Instructional models in social science education - Harwi; Zulaikah Esti; Tisa Apriah; Khodar Erwanti; Yayan Sudrajat (PT. Lancar Media Komunikasi, 2022)
The purpose of this article is to provide learning models that are suitable for use in social studies learning so that learning objectives can be achieved. Competency Standards and Basic Competencies of Social Sciences (IPS) at the Junior High School (SMP) level, covering study materials: sociology, history, geography, economics. The study material became the subject of Social Sciences (IPS). Problem-based learning is also one of the instructional models that can be used. Keywords: Instructional Models, Problem Based Learning